Factors associated with Incomplete Colonoscopy in Symptomatic Elderly Patients - Sufian, Arif Rukaini; Sainal, Mohd. Yusof; Elagili, Faisal; Aidid, Edre; Md Nor, Azmi (2021)
OBJECTIVES Colonoscopy is the gold standard for the investigation of lower GI symptoms. As Life expectancy in Malaysia has increased more colonoscopies are performed among older patients with GI symptoms, scant data about their risk factors for incomplete colonoscopy. The aim of our study was to evaluate significant risk factors for incomplete colonoscopy among older patients ≥ 65 years old. METHODOLOGY Data for patients who underwent colonoscopy from 2018 to 2020 were reviewed. The relationship between incomplete colonoscopy and demographics, patient characteristics, and other factors was assessed using univariate and multivariate analyses. RESULTS 108 patients (56% male patients) were recruited. The cecal intubation rate was 67%. By univariate analysis, increment increase age, poor colon preparation, cancer and diverticular were significant risk factors for incomplete colonoscopy. On multivariate analysis, the only factor associated with incomplete colonoscopy was poor bowel cleansing (p = 0.002). CONCLUSION In this study older patients were more likely to have an incomplete colonoscopy exam. The factors most strongly associated with incomplete colonoscopy was poor colon preparation. Older patient's bowel preparation is target on which we should act to improve performance.